Identifying and testing the probability distribution of earthfill dam breach parameters for probabilistic dam breach modeling - Alexandre Ângelo Carmo Luiz daSilva; Julian Cardoso Eleutério (Journal of Flood Risk Management, 2023)
Abstract The main goal of this study is to identify the probability distribution of earthfill dam breach parameters using a dam failures database (3861 observations). This work looks to fill the lack of studies observed, using an extensive database instead of empirical models, plausible values, or small databases. It is, expected that this will contribute to the development of probabilistic dam breach inundation maps instead of deterministic mapping. Four parameters were selected: (i) side slope, (ii) height, (iii) width, and (iv) formation time. To identify the best‐fit distributions, a correlation analysis was performed and a comparative analysis was undertaken by groups related to dam and failure properties such as dam type, material erodibility, magnitude, failure mode, and others. These steps defined samples with 33–311 observations. The results demonstrate that dam breach parameters might be considered independent of each other and are affected by factors such as side slope by failure mode and bottom width by dam shape. The probabilistic case study indicated that deterministic dam breach models predominantly produce conservative results of breach peak outflow.